Simulation of the risks of the safe operation of oil pipelines - Stepova, Olena; Adamski, Mariusz; Stepovy, Yevhen (Academic journal Industrial Machine Building Civil Engineering, 2022)
The development of practical aspects of environmental safety requires taking into account the necessary parameters of the tech-nical condition of equipment, namely oil pipelines, including their operating conditions, climatic features of the regions, stand-ardized risk and safety parameters, and residual resource based on reliability and durability indicators. On the basis of the electrochemical corrosion mathematical pipeline model in the insulating coating crack under the action of an aggressive electrolytic medium towards the pipeline metal, the dependence was obtained that allows to calculate the corrosion depth of the pipeline wall during the work of macro-galvanic corrosion couples in the conditions of stable and periodic stay of the aggressive solution in the damaged zone. The advantage of this model is the ability to predict the development of corrosion over time regardless of the corrosive electrolyte chemical composition, the possibility of obtaining necessary design parameters for operated structures. The developed dependencies of the pipeline section сorrosion depth make it possible to plan rationally the repair work, to predict the real terms of the structure work, to review the operation mode, etc. The obtained results allow us to more reliably evaluate the bearing capacity of structures that operate in conditions of aggressive medium with cracks